Connecting Sustainability Organizational Models with SDGs (2023)
The scientific works have been divided into 10 chapters. Hence, each chapter deeper analyzes the conference’s main topic. Thus, focusing on the study of the social dimension of sustainability from the human resource management point of view, several studies analyze its influence on social performance, as well as its consideration when applying quality management principles and practices as a driver to the social dimension of the organization since these practices could lead to the development of a sustainable orientation. Additionally, it is also important to analyze how work-family conflict and professional stress among financial workers and their relationships levers to burnout syndrome. Another key point is the role of women in the economy as the performance of organizations has a great deal with gender diversity from its triple dimension (economic, social, and environmental). Moreover, based on the concept of Gender Equality presented in the United Nations’ Sustainable Development Goals, the gender-role perspective is strictly related to the ECG.Cadascun dels 10 capítols inclosos en aquest llibre aprofundeix en l’anàlisi del tema principal de la II Conferència Internacional d’Economia del Bé Comú (2022). Així, centrant-se en l’estudi de la dimensió social de la sostenibilitat des del punt de vista de la gestió dels recursos humans, diversos estudis analitzen la seva influència en el rendiment social, així com la seva consideració a l’hora d’aplicar els principis i les pràctiques de gestió de la qualitat com a motor de la dimensió social de l’organització, ja que aquestes pràctiques podrien conduir al desenvolupament d’una orientació sostenible. A més, també és important analitzar com el conflicte treball-família i l’estrès professional entre els treballadors financers i les seves relacions provoquen la síndrome de ‘burnout’. Un altre punt clau és el paper de la dona en l’economia, ja que el rendiment de les organitzacions té molt a veure amb la diversitat de gènere des de la seva triple dimensió (econòmica, social i ambiental). A més, a partir del concepte d’igualtat de gènere presentat als Objectius de Desenvolupament Sostenible de les Nacions Unides, la perspectiva del rol de gènere està estrictament relacionada amb l’economia del bé comú.
Keywords: Sustainable Development; Corporate Sustainability; Sustainable Development Goals; Sustainable Supply Chain Management; Economy for the Common Good